Estimating Rupture Front of Large Earthquakes Using a Novel Multi-Array Back-Projection Method - Du, Hailin (Frontiers in Earth Science, 2021)
Ruptured front obtained from high frequency energy radiation is the key to understand the complex source. It is commonly observed that rupture fronts derived from different arrays often show some variations due to the obvious difference of the positioning accuracy of the far-field array between azimuth and the epicentral distance. We developed a new multi-array back-projection method based on the classical back-projection method, and applied the method to the 2015 Mw7.8 Nepal earthquake. The back azimuth information with small error is separated from the classical back-projection results, and the azimuth intersection of multiple arrays is used to obtain more accurate spatial and temporal distribution information of the source rupture fronts